Hubungan HbA1C Dengan Kadar Kreatinin Pada Penderita Diabetes Melitus Type 2 Di Rumah Sakit Krakatau Medika Cilegon: IND - Purwanto, Arina Emy; Listiawati, Enny (Politeknik Negeri Jember, 2024)
Diabetes Mellitus has become a global health problem due to a significant increase in its prevalence. Hyperglycemia, or elevated blood glucose levels, is a hallmark of diabetes mellitus and is caused by either insufficient insulin production by pancreatic beta cells or reduced insulin sensitivity in target cells. HbA1C examination is one of the glycemic controls in the assessment of type 2 diabetes mellitus. Good glycemic control is crucial for individuals with diabetes mellitus, as complications can arise from poor glycemic control. One common complication is diabetic nephropathy, which is a leading cause of chronic kidney failure, necessitating patients to undergo dialysis therapy or kidney transplantation , and can be diagnosed by serum creatinine levels examination. The aim of this study was to determine the relationship between HbA1C and serum creatinine levels in patients with type 2 Diabetes Mellitus at Krakatau Medika Hospital in Cilegon. The research employed an observational analytic method with a cross-sectional design. The data used were primary data obtained through quota sampling, with a population of 41 type 2 DM patients who met the inclusion and exclusion criteria. Using Pearson correlation test, the result showed a p-value of 0.031 (p < 0.05), indicating a significant relationship between HbA1C levels and creatinine levels. The value of r = 0.337 indicated a weak positive correlation between HbA1C and creatinine levels. From this study, it could be concluded that there was a significant weak positive HbA1C correlation with creatinine levels at Krakatau Medika Hospital in Cilegon.